Predictive Factors for Local Recurrence and Incomplete Resection of Early Gastric Cancer Treated by Endoscopic Resection: A Western Experience - Fábio Yuji Hondo; Fauze Maluf-Filho; Humberto Setsuo Kishi; Ricardo Sato Uemura; Luciano Okawa; Ivan Cecconello; Paulo Sakai (Canadian Journal of Gastroenterology)
BACKGROUND: Early gastric cancer (EGC) is defined as adenocarcinoma limited to the mucosa or submucosa regardless of lymph node involvement. Local EGC recurrence rates have been described in up to 6% of cases.